Penerapan Sequence of Service Oleh Waiter Saat Dinner Di Restoran Remedy, Four Seasons Vail, Colorado, USA - Realdi, I Kadek Deva; Koeswiryono, Dika Pranadwipa (Jurnal Ilmiah Pariwisata dan Bisnis, 2025)
Restoran memiliki peran penting dalam memberikan pelayanan yang berkualitas kepada tamu. Sequence of Service adalah tahapan layanan yang dilakukan oleh pramusaji untuk memastikan pengalaman bersantap yang optimal. Penelitian ini bertujuan untuk menganalisis penerapan Sequence of Service oleh pramusaji saat dinner di Restoran Remedy serta mengidentifikasi aspek layanan yang masih perlu ditingkatkan. Penelitian ini menggunakan metode kualitatif dengan teknik observasi dan wawancara kepada pramusaji dan supervisor di restoran. Hasil penelitian menunjukkan bahwa sebagian besar tahapan Sequence of Service telah diterapkan dengan baik, dengan tingkat kepatuhan mencapai 80-90%. Namun, terdapat dua aspek yang masih belum konsisten dilakukan oleh pramusaji, yaitu menanyakan rasa makanan kepada tamu dan menawarkan kopi atau teh. Kesimpulan dari penelitian ini menunjukkan bahwa meskipun Sequence of Service sudah berjalan sesuai prosedur, masih diperlukan peningkatan dalam beberapa aspek layanan untuk meningkatkan kepuasan tamu. Oleh karena itu, disarankan agar restoran memberikan pelatihan rutin bagi pramusaji, memperketat pengawasan supervisor, serta memastikan SOP layanan diterapkan secara konsisten untuk meningkatkan kualitas pelayanan di Restoran Remedy. This research aims to create an innovative culinary creation by utilizing a traditional fermented ingredient, tempoyak, in chicken curry. Tempoyak is fermented durian flesh, typically used in fish-based dishes. This innovation combines the distinctive acidity of tempoyak with the rich spices of chicken curry. The fermentation process takes a week, then the tempoyak is cooked with chicken and spices to create a distinctive flavor and soft texture. Sensory testing by six panelists, including visual, aroma, and taste assessments, showed positive responses, particularly for its flavor and aroma. Furthermore, the low production costs make this dish economically viable. This research demonstrates that tempoyak chicken curry could become a new variant in Indonesia's traditional culinary herita The restaurant plays an important role in providing quality service to guests. Sequence of Service refers to the stages of service performed by waitstaff to ensure an optimal dining experience. This study aims to analyze the implementation of the Sequence of Service by waiters during dinner at Remedy Restaurant and to identify aspects of the service that still need improvement. This research uses a qualitative method with observation and interview techniques conducted with the waitstaff and supervisor at the restaurant. The results show that most stages of the Sequence of Service have been well implemented, with a compliance rate of 80–90%. However, there are two aspects that are still inconsistently carried out by the waitstaff: asking guests about the taste of their food and offering coffee or tea. The conclusion of this study indicates that although the Sequence of Service is generally being followed according to procedure, improvements are still needed in certain aspects to enhance guest satisfaction. Therefore, it is recommended that the restaurant provide regular training for the waitstaff, strengthen supervisor oversight, and ensure that service SOPs are consistently applied in order to improve service quality at Remedy Restaurant.